1969
DOI: 10.1002/1097-0142(196901)23:1<152::aid-cncr2820230120>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous squamous cell carcinoma of the oral cavity

Abstract: Verrucous‐type oral tumors have been reviewed. This variety of epidermoid carcinoma of the oral cavity presents as a warty growth in patients who have a history of chewing tobacco and poor oral hygiene. They are slow‐growing, locally invasive, and do not metastasize to lymph nodes in our experience. In five of these patients, the microscopic pattern was that of a well‐differentiated squamous cell carcinoma. The others presented the classical histologic pattern of verrucous carcinoma. No difference was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
5

Year Published

1970
1970
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(47 citation statements)
references
References 4 publications
5
37
0
5
Order By: Relevance
“…Another study involving 30 cases of laryngeal VC also showed that surgery is the optimal therapy but that radiation and even chemotherapy can be used as alternatives for inoperable cases [20]. Although the older literature raised the issue of radiotherapy-related anaplastic or malignant transformation in VC [3,9,[21][22][23][24][25], this has clearly been refuted. Radiotherapy is now an accepted treatment modality for inoperable VC or for patients who are poor surgical candidates [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study involving 30 cases of laryngeal VC also showed that surgery is the optimal therapy but that radiation and even chemotherapy can be used as alternatives for inoperable cases [20]. Although the older literature raised the issue of radiotherapy-related anaplastic or malignant transformation in VC [3,9,[21][22][23][24][25], this has clearly been refuted. Radiotherapy is now an accepted treatment modality for inoperable VC or for patients who are poor surgical candidates [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is great difficulty in diagnosing tumors with these limited changes, and the terminology is widely variable. Pathologists use various descriptive terms such as 'verrucous carcinoma with focal dysplasia and/or invasion', 'well differentiated squamous cell carcinoma with verrucous features', 'focus of squamous cell carcinoma arising within a verrucous carcinoma', 'verrucous squamous cell carcinoma' [9], and 'hybrid' verrucous carcinoma [10]. There is a distinct lack of standard nomenclature, and, although these ''in between'' type tumors are not uncommon, there are no robust studies assessing their clinical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Verrucous carcinoma is a rare variant of squamous cell carcinoma that presents in the head and neck with the most common sites being the oral cavity and larynx [1][2][3][4][5][6][7][8]. It is so uncommon, in fact, that verrucous carcinoma composes only 5% of tumors at these sites [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…Discussion VC represents 2-12 % of oral cancers, occurring mainly in older men; mean age of presentation is 69 years [7]. However some studies have reported equal sex distribution [16], and some with female predominance [6,12]. It is strongly associated with use of chewable form of tobacco and betel nut [17].…”
Section: Demographic Data Of the Analysed Samplementioning
confidence: 99%